Effect of low NH3 flux towards high quality semi-polar (11-22) GaN on m-plane sapphire via MOCVD - Omar, Al-Zuhairi; Shuhaimi, Ahmad; Makinudin, Abdullah Haaziq Ahmad; Abdul Khudus, Muhammad Imran Mustafa; Azman, Adreen; Kamarundzaman, Anas; Supangat, Azzuliani (Elsevier, 2018)
The effect of ammonia flux towards the quality of the semi-polar (11-22) gallium nitride thin film on m-plane (10-10) sapphire is presented. Semi-polar (11-22) gallium nitride epi-layers were obtained using a two-step growth method, consisting of high temperature aluminum nitride followed by gallium nitride via metal organic chemical vapor deposition. The surface morphology analysis via field emission scanning electron microscopy and atomic force microscopy of the semi-polar (11-22) gallium nitride has shown that low ammonia flux promotes two-dimensional growth with low surface roughness of 4.08 nm. A dominant diffraction peak of (11-22) gallium nitride was also observed via X-ray diffraction upon utilizing low ammonia flux. The on- and off-axis X-ray rocking curve measurements illustrate the enhancement of the crystal quality, which might result from the reduction of the basal stacking faults and perfect dislocation. The full width half maximum values were reduced by at least 15% for both on- and off-axis measurements.